The politics of eloquence : David Hume's polite rhetoric - Hanvelt, Marc, 1974- (University of Toronto Press, 2012)
Drawing on Hume's philosophical, historical, and popular writings, The Politics of Eloquence presents an understanding of rhetoric that can be properly ascribed to this important thinker, an understanding hitherto overlooked in the scholarly literature.